Appreciating situations of breakdown for researcher reflexivity. Issue 3 (September 2022) - Treacy, Danielle
Responding to the identified need for reflection, critique, and evaluations of appreciative inquiry (AI), a form of action research, this article presents a critical reflection on an application of AI in a cross-cultural music education research project. AI was selected as it appeared to both have potential for addressing the complexities related to power imbalances, ethnocentrism, and coloniality inherent in a project aiming to co-develop music teacher education in Finland and Nepal, and because its 4D model supported the co-constructing of visions, which was central to the project. The critical reflection presented in this article focused on three situations of breakdown that occurred during the research process. Analysis of these breakdowns highlighted the need for researchers to engage responsibly in research as participants, account for dreaming as an unevenly distributed capacity when working with visions or aspirations, and develop skills facilitating collaborative spaces that cultivate listening for and appreciating difference. The article concludes by recognising the limitations of undertaking this reflection independently rather than collaboratively and by cautioning against the instrumentalization of appreciation, calling instead for sincere appreciation . Overall, the article contends that the process of identifying and generating new understandings of breakdowns is a powerful approach for stimulating researcher reflexivity.